2014
DOI: 10.3109/00365521.2014.894120
|View full text |Cite
|
Sign up to set email alerts
|

Difficult cannulation as defined by a prospective study of the Scandinavian Association for Digestive Endoscopy (SADE) in 907 ERCPs

Abstract: If the increasing rate of PEP is taken as defining factor, the wire-guided cannulation of a native papilla can be considered difficult after 5 min, five attempts, and two pancreatic guide-wire passages when any of those limits is exceeded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 28 publications
7
102
2
6
Order By: Relevance
“…Notably, absent as an independent risk was contrast injection, which was overshadowed by deep wire passage. Subsequent studies have corroborated the risk of pancreatic wire passage, especially during guidewire cannulation [12,13]. Most studies of Bdouble-wire^technique to cannulate bile duct also suggest increased risk [14].…”
Section: Procedure-related Factorsmentioning
confidence: 96%
“…Notably, absent as an independent risk was contrast injection, which was overshadowed by deep wire passage. Subsequent studies have corroborated the risk of pancreatic wire passage, especially during guidewire cannulation [12,13]. Most studies of Bdouble-wire^technique to cannulate bile duct also suggest increased risk [14].…”
Section: Procedure-related Factorsmentioning
confidence: 96%
“…10 There is wide disparity but the most accurate overall risk of PEP from prospective studies ranges from 3%-10%. 1,4,5,[11][12][13][14][15][16] A survey of prospective studies in 2007 reported that about 10% of PEP cases were graded as severe and the overall mortality of PEP was 3%. 1 …”
Section: Post-ercp Pancreatitismentioning
confidence: 99%
“…ERCP may not be feasible in patients with malignant gastric outlet or duodenal obstruction, and rarely if there is an inability to cannulate the papilla or transverse a common bile duct (CBD) stricture. 23 When ERCP fails, percutaneous drainage, surgical bypass, and EUS-guided biliary drainage (EUS-BD) are alternative options. [24][25][26] The rates of technical and clinical success have been high with EUS-BD (86%-98% and 88%-94%, respectively), although complication rates have been high as well (9%-26%).…”
Section: Bile Duct Drainagementioning
confidence: 99%